Buku Panduan Perpustakaan Universiti Sains Malaysia (Guidebook Universiti Sains Malaysia Library) 2019 - Perpustakaan, Universiti Sains Malaysia (Perpustakaan Universiti Sains Malaysia, 2019)
Customers must display their smart cards upon entering the Library. Customers must adhere to the Dress Code as stipulated by the University. Customers are requested to observe silence. Mobile phone must be put on silent mode in the Library. Eating and drinking (except for plain water) is prohibited in the Library